Research progress of stem cell-derived RPE cell transplantation therapy for retinal degenerative diseases - Tian-Yue Cao (Guoji Yanke Zazhi, 2017)
Age-related macular degeneration(ARMD)and Stargardt's macular dystrophy(SMD)are two kinds of degenerative retinal diseases that respectively lead to irreversible vision loss of the elderly and juvenile population. However, the severe visual impairment in dry ARMD and SMD remains untreatable. In recent years, with the advancement of stem cell technology, stem cell-derived RPE cell transplantation therapy of retinal degeneration has become new research hotspot and direction. This article reviewed the progress of stem cell based approaches for treating retinal degenerative diseases and discussed the prospect and challenges in this field.